Fatty acids as novel treatment options for Pseudomonad and Staphylococcal infection. Issue 7 (10th July 2020) - Ukachukwu, Faith; Snyder, Lori; Alany, Raid
Abstract : Pseudomonas aeruginosa and Staphylococcus aureus are bacteria pathogens that cause a myriad of infections affecting various sites in the body including the eyes, ears, lungs, skin, heart, bones, and blood amongst others. These bacteria can be disseminated via the blood to other parts of the body away from the primary site of infection and consequences vary from mild to severe with death occurring in certain instances. Both bacterial infections can occur individually, as well as in co-infection resulting in even worse outcomes. P. aeruginosa and S. aureus exhibit multidrug resistance against current antibiotic treatment regimens, which accentuates the challenge in managing the infections caused by these bacteria. To prevent the looming era of untreatable bacterial infections, alternative treatment regimens that are cost effective and accessible are needed. To explore novel treatment options, twenty-five organic compounds comprising fatty acids and their derivatives were screened for antibacterial activity in broth microdilution assay to determine the minimum inhibitory concentration and minimum bactericidal concentration against both P. aeruginosa and S. aureus . Five candidates (N–nonanoic acid, butyric acid, heptanoic acid, palmitoleic acid, and isopropyl myristate) were effective against P. aeruginosa . Seven candidates (N–nonanoic acid, palmitoleic acid, tridecanoic acid, sebaic acid, undecanoic acid, monolaurin, and monocaprin) were effective against S. aureus . Candidates such as N–nonanoic acid and palmitoleic acid were effective against both P. aeruginosa and S. aureus, demonstrating that the same fatty acids show potential to be used against both Gram negative and Gram positive bacterial infections.